The gender of constitutional jurisprudence - Baines, Beverley 1941-; Rubio-Marín, Ruth (Cambridge University Press, 2005)
To explain how constitutions shape and are shaped by women's lives, the contributors to this volume examine constitutional cases pertaining to women in twelve countries. Analyzing jurisprudence about reproductive, sexual, familial, socio-economic, and democratic rights, they focus constructively on women's claims to equality, asking who makes these claims, what constitutional rights inform them, how they have evolved, what arguments work in defending them, and how they relate to other national issues. Their findings reveal significant similarities in outcomes and in reasoning about women's constitutional rights in these twelve countries, challenging the tradition of distinguishing constitutional jurisprudence depending on whether the country has a written or unwritten constitution, subscribes to civil or common law, is a federal or unitary state, limits constitutional adjudication to the public domain, accords international norms binding or subject to incorporation force, or relies on a specialized or general court to adjudicate constitutional matters